RESPONSIBILITY TO BE A DEFENDER OF THE COUNTRY - Fozilov Umidjon Fozilovich (Galaxy International Interdisciplinary Research Journal, 2021)
Establishment of the Armed Forces of the Republic of Uzbekistan on August 31, 1991, the Law "On the Foundations of State Independence of the Republic of Uzbekistan" was adopted, an important document that enabled the young republic to implement military policy. In other words, the statement of the law "On state independence of the Republic of Uzbekistan" served as a legal basis for the formation of our Armed Forces.